Anaerobic digestion of organic fraction from hydrothermal liquefied algae wastewater byproduct. (January 2018) - Fernandez, Sebastian; Srinivas, Keerthi; Schmidt, Andrew J.; Swita, Marie S.; Ahring, Birgitte K.
Graphical abstract: Highlights: HTL wastewater can be co-digested together with clarified manure. High methane yields were obtained at up to 30% (v/v) HTL wastewater in manure. Highest methane production was 327.2 and 263.4 mL/g VSin for AgTet and AgChlr respectively. Methane production was reduced at concentrations greater than 40% (v/v) HTL wastewater. There was significant accumulation of pyrazines, pyrrolidines and chloride salts above 40% (v/v) HTL. Abstract: The wastewater stream from hydrothermal liquefaction (HTL) process used in biofuel production, contains a large amounts of organic compounds where several can be regarded as environmentally hazardous and requires significant treatment before disposal. In this study, semi-continuous anaerobic digestion is used to degrade the organic fraction of wastewater streams from HTL of the algae Tetraselmis (AgTet) and Chlorella (AgChlr). Results indicated high methane yields at 20–30% (v/v) HTL wastewater together with clarified manure, producing 327.2 mL/gVSin (or volatile solids in feed) for AgTet and 263.4 mL/gVSin for AgChlr. There was a significant reduction in methane production at concentrations higher than 40% (v/v) HTL wastewater in the feed, possibly due to the accumulation of chloride salts or inhibitory compounds such as pyridines, piperidines and pyrrolidines. This was further confirmed by comparing COD, salt and the ammonia concentrations of the effluents after anaerobic digestion at different concentrations of wastewater in manure.